PENYIDIKAN TINDAK PIDANA PENGEROYOKAN OLEH ANAK DI WILAYAH HUKUM KEPOLISIAN SEKTOR PEKANBARU KOTA - Vivi Kartika Sari; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The law in Indonesian lately under the spotlight from all levels of society. That happens because the law is expected as penertib instrument, tool guard the balance between the public interest with the interests of an individual, as a catalyst for driving the process of change to protect the public, are still far from such expectations. From the wording of Article 90 is clear, straightforward and resolute that both child victims of child offenders, and child witnesses should be given protection and handling as possible. Thus, the main principle of the protection of children, it is good for the child's best interest, non-discrimination, survival and development, as well as the principle of children's participation can be assured.First, keep children from environmental influences and people who are not healthy and always gave the example directly so that children are not susceptible to things that are bad and also provide protection to the child if the child needs help in their time of trouble.Second, to order an investigation into the case of children, the investigator shall ask for consideration or suggestion of Supervisor Community after criminal offenses reported or brought. If deemed necessary, the investigator may meinta consideration or advice from education experts, psychologists, psychiatrists, religious leaders, Professional Social Workers or Social Welfare Workers, and other experts, even in terms of conducting the examination of child victims and child witnesses, investigators are required to request social report from the Professional social Worker or social Welfare WorkersThird, in addition to facilitate the activities of the investigator in overcoming the obstacles that occur in the case by getting information from the victims and the perpetrators, the investigation process can run properlyKeyword: investigation-criminal offense-child